An Introduction to Geoffrey Chaucer - Pugh, Tison (Book collections on Project MUSE., 2013)
An overview of Chaucer's work, focusing on the most canonical texts, such as Canterbury Tales and Troilus and Criseyde, while also providing some analysis of his minor works.